2021
DOI: 10.1371/journal.pone.0246862
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the impact of obesity on hormonal and metabolic perturbations in polycystic ovary syndrome phenotypes in Indian women

Abstract: Polycystic ovary syndrome is a complex endocrinopathy with heterogeneous presentation and multifactorial etiology. We have undertaken this case-control study to compare metabolic and endocrine characteristics in different phenotypic subgroups of women with PCOS and the impact of obesity on them. Women with PCOS (n = 489) were classified into 4 phenotypes according to Rotterdam criteria. Comparisons of clinical, biochemical and hormonal parameters were performed across all phenotypic groups of PCOS and with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 67 publications
(101 reference statements)
1
13
0
Order By: Relevance
“…However, PCOS is a highly heterogenic syndrome, with variable manifestations in different ethnic and age groups [8], so different cut-offs should be used for MBI, IR, hirsutism and other clinical signs [9]. Obesity, for example, is often observed in PCOS patients and known as an accentuating factor [10], albeit, for Asian ethnic groups, the connection between PCOS and obesity is less pronounced [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, PCOS is a highly heterogenic syndrome, with variable manifestations in different ethnic and age groups [8], so different cut-offs should be used for MBI, IR, hirsutism and other clinical signs [9]. Obesity, for example, is often observed in PCOS patients and known as an accentuating factor [10], albeit, for Asian ethnic groups, the connection between PCOS and obesity is less pronounced [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…AMH was associated with the pathophysiology of reproductive dysfunction in PCOS and reflects PCOS status, therefore it may also be useful in PCOS diagnosis [40]. Dadachanji, et al [41] revealed the importance of clinicians concurrently employing Rotterdam criteria along with obesity status for ascertaining accurate disorders in the course of PCOS status.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, multiple MR studies revealed that obesity potentially causes PCOS, all of which exclusively used body mass index (BMI) as the surrogate anthropometric measure of obesity [ 25 28 ]. However, BMI is essentially a marker of general obesity whereas central obesity in particular seems to confer a formidable influence on PCOS pathogenesis [ 16 18 ]. Moreover, the use of multiple anthropometric traits could yield not only complementary but also exclusive information.…”
Section: Introductionmentioning
confidence: 99%